Valoración de la calidad del agua de la quebrada los molinos, utilizada para consumo humano, parroquia Valladolid, cantón Palanda, provincia Zamora Chinchipe - Jiménez Macau, Mayra Lorena (2014)
This research was conducted in the watershed Los Molinos, Valladolid Parish, Zamora Chinchipe province. The study area comprises a surface of 1063.67 ha. The main research aim is to assess the water quality of the creek Los Molinos, which supplies drinking water to the town of Valladolid Parish. Two seasonal samples of physical-chemical, microbiological and biotic water were performed at four different spots distributed along the middle and lower areas of the creek; these results were used to determine water quality index (ICA), pollution index (ICO) and bioticindex in order to assess the quality of this resource in the area. In addition, interviews were performed to a random group of 81 persons, in order to identify problems that poor quality of the water cause in the researching area. It was determined that the water in the area presents percentages of coliform outside the ranges established in environmental legislation at both global and national levels, nevertheless water quality varies depending on the index used, obtaining values from very good to poor quality . As result, this research has arrived to the conclusion that problems in the area revolve around the progression of the cattle frontier in the watershed, so you can see a decreasing quality of water in the sampled points. It was also noted that, despite the different results found with the index used, they clearly relate resource regarding pollution.